Water the Flowers You Want to Grow? Evidence on Private Recognition and Donor Loyalty - Benjamin Bittschi; Nadja Dwenger; Johannes Rincke (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study donor loyalty in the context of church membership in Germany. Church members have to make substantial payments to their church but can opt out at any time. In a large-scale field experiment, we examine how private recognition for past payments affects church members' loyalty. We find that recognizing past payments in a letter significantly reduces opt-outs. This effect is driven by members in the bottom quartile of baseline payments to the church. Consistent with optimization frictions prior to the experiment, we observe a spike in opt-outs immediately after treatment for particularly costly memberships.
Keywords: D64; C93; 330; private recognition; donor loyalty; charitable giving; field experiment; recurring donors